Celebration of the 300th Anniversary of the House of Romanov in the cities of the Volga region - Morgunov, Yaroslav V. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2022)
On the materials of the state archives of Samara, Kazan, Cheboksary and on published historical sources the article analyzes the preparations for the celebrations dedicated to the 300th anniversary ofthe Romanov dynasty. It is shownthat preparationsforthe holidaytook on a universal  character, all segments of the population, independent of class, national, religious affiliation, were involved in the process of this preparation. Programs of celebrations are analyzed, they depended on a specific city, its material capabilities and the composition of the population. The festive program could include additional elements that differ in cities on the Volga. The author concludes that such large-scale festive events covering all segments of the population were an attempt to consolidate Russian society around the monarchy and the figure of Emperor Nicholas II after the revolutionary events of 1905–1907 and in the context of the beginning of a new social rise.